HAK PENGASUHAN ANAK DI BAWAH UMUR SEBAGAI AKIBAT PERCERAIAN - Agung Pratama; Khairani Bakri (Reformasi Hukum Trisakti, 2023)
The Cases of disputes over child custody (hadhanah) due to divorce are common in society. For underage children, Article 105 (1) KHI provide hadhanah to their mothers. However, court may determine otherwise through a mediation. The research’s problem: what are the provisions regarding hadhanah as result of divorce according to the Marriage Law, and is the Decision of PA Sukadana No: 1057/Pdt.G/2019/PA. Sdn, is in accordance with marriage laws. The research conducted in normative and descriptive analytical legal research, using secondary data obtain through literature studies. The data is analyzed qualitatively and conclusions are drawn using deductive understanding. The conclusion is that the Marriage Law does not definitively regulate the hadhanah. Hadhanah is regulated in Article 105 paragraph (1) KHI, namely "A custody of a child who is not yet mumayiz or not yet 12 years old is the right of the mother". The Contents of the Amar Decision of PA Sukadana which stipulates hadhanah to the father (Defendant) and after the child is 12 years old hadhanah is determined based on the wishes of the child, are not in accordance with the provisions of KHI, but can be justified based on Supreme Court Regulation Number 1 of 2016.